Nitrogen-doped biochar derived from watermelon rind as oxygen reduction catalyst in air cathode microbial fuel cells. (15th May 2019) - Zhong, Kengqiang; Li, Meng; Yang, Yue; Zhang, Hongguo; Zhang, Bopeng; Tang, Jinfeng; Yan, Jia; Su, Minhua; Yang, Zhiquan
Graphical abstract: Highlights: Watermelon rind acts as both rich-nitrogen source and carbon framework in synthesis. The high electrochemical performance is ascribed to active CN bonds and high contents of pyridinic-N and graphitic-N. WRC-700 possesses an outstanding electrochemical active area of 658.90 m 2 g −1 . The microbial fuel cell using the WRC-700 cathode achieves the low charge transfer resistance of 20.63 Ω. WRC-700 is a highly cost-effective and potential replacement to commercial Pt/C for microbial fuel cells. Abstract: Cathodic electrocatalyst is critical to the performance of microbial fuel cells. Developing cost-effective and efficient catalyst for oxygen reduction reaction is therefore an important step towards wider application of microbial fuel cells. Herein, we report a cost-effective and environment-friendly strategy for synthesis of nitrogen-doped hierarchically porous carbon with watermelon rind as a nitrogen-rich and high stability precursor and the biochar is used as cathode catalyst in air cathode microbial fuel cells. In this study, the pyrolysis derivative, WRC-700, achieves a current density of redox peak of 0.19 mA cm −2, which is comparable to the Pt/C catalyst. There are more CN bonds and higher concentrations of pyridinic nitrogen and graphitic nitrogen in the carbon framework of WRC-700 catalyst resulting in an outstanding electrochemical active area of 658.90 m 2 g −1, functioning through a four-electron pathway toward oxygen reduction reaction process. The charge transfer resistance of 20.63 Ω is achieved by WRC-700 cathode, which is slightly smaller than Pt/C cathode (37.56 Ω). With experimental validation, we find that carbon from watermelon rind biomass can be considered as a superior alternative to non-metal catalyst in microbial fuel cell applications and envisage an enhanced power output from microbial fuel cells using the catalyst-modified cathodes.